Making civil society work, promoting democratic development : what can states and donors do? - HADENIUS, Axel (1996)
Discusses the importance of independent institutions and organizations for the consolidation of democracy. Looks at how these institutions are affected by external actors - most notably other organisations, the state and donor agencies. Presents a model for strengthening civil society.